Graphene Oxide Modified Bimetallic Al/Fe (Hydro)Oxides Doped Activated Carbon Composite for Efficient Adsorption of Hexavalent Chromium from Aqueous Solution - Tsheamo W. Mogale; Fisseha A. Bezza; Shepherd M. Tichapondwa; Evans M. N. Chirwa (Chemical Engineering Transactions)
The uncontrolled release of Cr(VI) poses significant risks to ecosystems, with studies showing that its concentrations in surface and groundwater frequently exceed safe limits for freshwater, wastewater, and soil. Cr(VI) is particularly hazardous due to its high solubility and mobility in water, as well as its ability to cause harm to humans and aquatic organisms even at trace levels. In this study, Al2O3@Fe2O3 nanoparticles doped activated carbon was synthesized via a co-precipitation method, using equimolar amounts of iron (Fe) and aluminium (Al) salts in the presence of finely ground wheat straw at a bimetal-to-straw mass ratio of 10:1. After co-precipitation, the mixture was dried and chemically activated with potassium hydroxide (KOH) at 500°C, which facilitated the formation of a porous carbon structure. Subsequently, the Al2O3@Fe2O3 doped activated carbon was grafted with an equal mass of graphene oxide (GO), freeze-dried, and used for adsorbing Cr(VI) from water. The adsorption performance of the material was assessed at various initial concentrations of the adsorbate, different adsorbent dosages, and pH levels. The adsorbent achieved up to 99.9% removal of Cr(VI) from a 100 mg/L Cr(VI) contaminated solution. It exhibited a broad pH range adsorption potential, effectively functioning across a pH range of 4 to 7, with the highest adsorption occurring at lower pH levels. The grafting of GO significantly improved the adsorbent’s capacity, enabling complete elimination of residual Cr(VI). The isotherm adsorptive study obeyed to the Langmuir isotherm, with a maximum adsorptive capability ( ?? ?????? ) of 95.17 mg/g and a 99.24% fit to the model. An extremely porous structure was displayed using scanning electron microscopy (SEM) with uniformly dispersed Al2O3@Fe2O3 nanoparticles on the porous graphene oxide/carbon matrix. The Fourier Transform Infrared Spectroscopy (FTIR) study displayed high surface area of the adsorbent with rich oxygen containing functional groups.